Similarity and Variance of Color Difference Based Demosaicing - R. Niruban; T.Sree Renga Raja; R. Deepa (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The aim of the project is to find the missing color samples at each pixel location by the combination of similarity algorithm and the variance of colour difference algorithm. Many demosaicing algorithms find edges in horizontal and vertical directions, which are not suitable for other directions. Hence using the similarity algorithm the edges are found in different directions. But in this similarity algorithm sometimes the horizontal and vertical directions are mislead. Hence this problem can be rectified using the variance of colour difference algorithm. It is proved experimentally that this new demosaicing algorithm based on similarity and variance of colouyr difference has better colour peak signal to noise ratio (CPSNR). It has better o0bjective and subjective performance. It is an analysis study of both similarity and colour variance algorithms. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7048